IMPLEMENTASI SISTEM INFORMASI RUMAH SAKIT UNTUK SUBSISTEM LABORATORIUM DENGAN FRAMEWORK PRADO - Handoyo, Eko; Budi Prasetijo, Agung; Mardiatmo Nur Hidayat, Dwi (TEKNIK, 2008)
Nowadays, the need of an information for some hospital is getting bigger. This Hospital Information Systemapplication is made to be based on web by using Prado framework based on PHP programming languageand MySQL as its databases. This research include application scheme using object oriented approach,database scheme, and also examination from application as a wholeIn its making, this application adaptedwith the requirement of a hospital in general such as facility for requesting of examination disease atlaboratory, queue information of test request, record-keeping of test result of a patient at medical laboratory,pathology, and bacteriology, blood request for patient at blood bank of hospital, and also result informationof laboratory test of a patient. The result of the application examination show this information system canwork if input condition have been full filed. Process which desirable for example login and user registrationprocess, data addition, data change, data abolition, and the data seeking at system. This application earn togive queue information of test request, service for the blood requesting, and also result information oflaboratory test of a patient.